EVALUATION INTERNATIONALIZATION PROGRAMS OF CREATIVE INDUSTRY MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) IN PURBALINGGA: AN ANALYTICAL HIERARCHY PROCESS (AHP) METHOD - Suliyanto, Suliyanto; Novandari, Weni; Yunanto, Ary (Faculty of Economics and Business Universitas Jenderal Soedirman, 2019)
This study aims to evaluate the program of internationalization of UMKM Creative Industries in Purbalingga . Respondents in this study are the SMEs Creative Industries business people who are considered to have knowledge about the Creative Industry in Purbalingga. Data collection using in-depth interviews, questionnaires, and Focus Group Discussion (FGD). Data analysis used is descriptive qualitative and Analytical Hierarchy Process (AHP). Based on the analysis concluded that several factors lead to non-optimal of Creative Industry MSEs internationalization programs sequences was lack of financial, managerial capabilities, lack of information, government support, and the international environment. In order to optimal, Creative Industry of MSMEs internationalization programs should be conducted to use counseling and sustainable facilitation, in which the government and successful entrepreneurs in the international market help entrepreneurs MSMEs creative industries in Purbalingga to succeed in the international market.